Promoting Menstrual Health Through Nutritional Education and Peer-Based Interventions in Adolescent Girls: A Scoping Review - Putu Ayu Karisma; Apoina Kartini; Siti Fatimah Pradigdo (Journal of Health Promotion and Behavior, 2025)
Background: Menstruation, a normal part of puberty, is frequently misinterpreted because of societal stigma and limited access to proper education. Educational settings and peer-based programs are key in enhancing both menstrual and nutritional health, which are vital to supporting the overall well-being of adolescent girls. This Study aims to explore the factors influencing the promotion of menstrual health through nutrition education and peer-based interventions for adolescent girls using a scoping review methodology. Subject and Method: This scoping review was conducted using data obtained from PubMed Central, Science Direct and Google Scholar. The target population includes adolescent girl related to their menstrual health, nutritional education and peer-based intervention. A search was conducted using the keywords “Menstrual health" AND "nutritional education" AND "peer-based interventions" AND ("adolescent girls" OR "teen girls" OR "adolescent health") AND ("menstruation" OR "menstrual hygiene" OR "menstrual health promotion") AND ("nutrition" OR "diet" OR "healthy eating") AND ("peer support" OR "peer education" OR "peer-led programs"), yielding 4.245  articles, which were then filtered down to 7 relevant articles after applying a 10-year time frame. Results: Several factors influence the promotion of menstrual health through nutrition education and peer-based interventions for adolescent girls. These include social support from peers, skills-based education, family involvement (especially mothers), sufficient nutrition literacy, psychosocial factors such as self-confidence and self-control, the role of schools as a health education platform, and the theoretical models used in the program, such as the Theory of Planned Behavior. Conclusion: Peer-led and skills-based education improves health outcomes for adolescent girls. Combining peer support, family involvement, and active learning enhances program success. Schools and communities should adopt these models to address adolescent health issues effectively.